Bipolenins K–N: New sesquiterpenoids from the fungal plant pathogen Bipolaris sorokiniana - Phan, Chin-Soon; Li, Hang; Kessler, Simon; Solomon, Peter S.; Piggott, Andrew M.; Chooi, Yit-Heng (Beilstein Journal of Organic Chemistry, 2019)
Chemical investigation of the barley and wheat fungal pathogen Bipolaris sorokiniana BRIP10943 yielded four new sativene-type sesquiterpenoid natural products, bipolenins K–N (1–4), together with seven related known analogues (5–11), and a sesterterpenoid (12). Their structures were determined by detailed analysis of spectroscopic data, supported by TDDFT calculations and comparison with previously reported analogues. These compounds were evaluated for their phytotoxic activity against wheat seedlings and wheat seed germination. The putative biosynthetic relationships between the isolated sesquiterpenoids were also explored.
Keywords: Bipolaris sorokiniana; phytotoxicity; sesquiterpenes; terpenes